2014
DOI: 10.3390/ma7032194
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Creep and Creep Damage in the γ-Titanium Aluminide Ti-45Al-2Mn-2Nb

Abstract: Gamma titanium aluminides (γ-TiAl) display significantly improved high temperature mechanical properties over conventional titanium alloys. Due to their low densities, these alloys are increasingly becoming strong candidates to replace nickel-base superalloys in future gas turbine aeroengine components. To determine the safe operating life of such components, a good understanding of their creep properties is essential. Of particular importance to gas turbine component design is the ability to accurately predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The creep problem the same as the fatigue problem needs to be solved urgently. The model research of the creep problem can be divided into 3 directions: (1) The creep model [1][2][3] was established on the basis of the creep strain rate, which is the key parameter by considering the creep activation Nomenclature: a i , b i , c i , d i , parameters about η i ; f 1 , f 2 , f 3 , parameters about σ 0.2 (MPa); k M1 , k M2 , adjustable variables; t 1 , varying loading time in (σ 1 , T 1 ) (h); t 2 , varying loading time in (σ 2 , T 2 ) corresponding to t 1 (h); t c, 1 , t c, 2 , creep rupture time (h); t i , creep time at a certain creep strain (h); E, Young modulus (MPa); M1, the creep time satisfies the normal distribution; M2, the creep time satisfies the log-normal distribution; T, T 1 , T 2 , temperature (°C); T m , melting point (°C); S M1, i , S M2, i , the standard deviations of creep time at a certain creep strain (h); X M1;i ; X M2;i , the average creep time at a certain creep strain (h); ε, total strain (%); ε c , creep strain (%); ε p , plastic strain (%); θ, temperature (°C); η 1 / % , η 2 / % , η 3 / % , η 4 , η 5 , parameters in creep model; ζ, relative creep time; σ, σ 1 , σ 2 , net sectional stress (MPa); σ 0.2 , yield strength (MPa) energy. The advantage is with a clear physical meaning, but the disadvantage is the low calculation accuracy leading that it is not easy to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…The creep problem the same as the fatigue problem needs to be solved urgently. The model research of the creep problem can be divided into 3 directions: (1) The creep model [1][2][3] was established on the basis of the creep strain rate, which is the key parameter by considering the creep activation Nomenclature: a i , b i , c i , d i , parameters about η i ; f 1 , f 2 , f 3 , parameters about σ 0.2 (MPa); k M1 , k M2 , adjustable variables; t 1 , varying loading time in (σ 1 , T 1 ) (h); t 2 , varying loading time in (σ 2 , T 2 ) corresponding to t 1 (h); t c, 1 , t c, 2 , creep rupture time (h); t i , creep time at a certain creep strain (h); E, Young modulus (MPa); M1, the creep time satisfies the normal distribution; M2, the creep time satisfies the log-normal distribution; T, T 1 , T 2 , temperature (°C); T m , melting point (°C); S M1, i , S M2, i , the standard deviations of creep time at a certain creep strain (h); X M1;i ; X M2;i , the average creep time at a certain creep strain (h); ε, total strain (%); ε c , creep strain (%); ε p , plastic strain (%); θ, temperature (°C); η 1 / % , η 2 / % , η 3 / % , η 4 , η 5 , parameters in creep model; ζ, relative creep time; σ, σ 1 , σ 2 , net sectional stress (MPa); σ 0.2 , yield strength (MPa) energy. The advantage is with a clear physical meaning, but the disadvantage is the low calculation accuracy leading that it is not easy to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be deduced that the SP creep behaviour of this γ-TiAl alloy is strongly dependent on the maximum principle stress, σ 1 . Previous studies have shown that tertiary creep in this alloy initiates due to microstructural instabilities [16], such as strain incompatibilities between lamellar grains [23], with uniaxial creep fracture surfaces displaying interlamellar and intergranular cracking [4]. Therefore, the nature of the cracking and the dependence of this alloy on σ 1 indicate that the lamellar microstructure strongly influences the SP creep behaviour, with rupture a result of microstructural degradation such as the consolidation of inter-lamellar cracks.…”
Section: Creep Damage and Rupture In The Sp Creep Testmentioning
confidence: 98%
“…To predict SP creep in γ-Ti-45Al-2Mn-2Nb a suitable creep model is required. One such model has been previously described [16] which uses the theta (θ) projection technique to relate creep behaviour to test conditions. This model also predicts creep rupture based on the accumulation of creep damage (W).…”
Section: A Finite Element Model Of the Small Punch Creep Testmentioning
confidence: 99%
See 2 more Smart Citations